(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
The novel is often understood as a form of writing that explores the self, society, and the relationships linking peoples and cultures across the world. In doing so, it foregrounds the notion of humanity and its values, seeking to embody them in social consciousness through narrative discourse that writes about the human being and searches for meaning in the dark labyrinths of existence. Because the Algerian novel is part of world literature in its aims and functions, its narrative discourse is rarely devoid of such values. This paper examines the human values carried by Algerian fiction and argues that they are frequently articulated through the author’s ideological positioning, cultural horizon, and worldview; therefore, values appear in the text as both ethical aspirations and narrative choices. Methodologically, the paper combines a conceptual discussion of values with a thematic-narratological reading that follows how values are ‘performed’ through character construction, plot conflict, and the distribution of voice.